A field analysis on the emergence of migrant entrepreneurs in Japan and their integration into the Japanese society - Karayılmaz, Kaan (Border Crossing, 2018)
Demographic change implies more than the aging of the Japanese population and causes socioeconomic and spatial structural transformation processes. Against the backdrop of demographic change, the issue of integrating migrants into Japanese society is gaining in importance and is increasingly drawing attention to economic policy decisions. The growth of new ethnic populations in Japan since 2000 has made ethnic businesses a matter of importance. The self-employed migrants in Japan includes very heterogeneous social situations. There are among those both low earners in precarious sectors as well as good earners in knowledge-intensive businesses. The different nationality of the interviewees in the analysis is justified by the fact that the process of self-employment is explained not only by the individual characteristics of entrepreneurs, but also by the social structures and cultural background of Japanese society and thus the independence from today's point of view. The public opinion on the migrants or migration to Japan and the opinion of migrants about Japanese society is the subject of the study, which explores migrant, Japanese and immigrant perspectives on migration, integration and self-employment.